2013
DOI: 10.1093/schbul/sbt166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interpersonal Trauma on the Social Functioning of Adults With First-Episode Psychosis

Abstract: Background: Social functioning is an important treatment outcome for psychosis, and yet, we know little about its relationship to trauma despite high rates of trauma in people with psychosis. Childhood trauma is likely to disrupt the acquisition of interpersonal relatedness skills including the desire for affiliation and thus lead to impaired social functioning in adulthood. Aims: We hypothesized that childhood trauma would be a predictor of poor social functioning for adults with psychosis and that further tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 39 publications
5
63
2
1
Order By: Relevance
“…However, when adjusting all analysis for gender, the differences we observed remained significant, suggesting exposure to trauma is indeed an important characteristic of such patients. In line with others [39][40][41][42] we observed in a previous study that exposure to adverse experiences during childhood is associated with poorer functional [25] and symptomatic [26] recovery; the fact that LO patients were more likely to have been exposed to trauma may hence play a role in their failure to return to their pre-morbid functional level.…”
Section: Discussionsupporting
confidence: 90%
“…However, when adjusting all analysis for gender, the differences we observed remained significant, suggesting exposure to trauma is indeed an important characteristic of such patients. In line with others [39][40][41][42] we observed in a previous study that exposure to adverse experiences during childhood is associated with poorer functional [25] and symptomatic [26] recovery; the fact that LO patients were more likely to have been exposed to trauma may hence play a role in their failure to return to their pre-morbid functional level.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with a first episode of psychosis and those with established schizophrenia who had experienced childhood trauma exhibited worse premorbid social and academic functioning compared with those without a history of childhood trauma (Schenkel et al 2005;Stain et al 2014). Childhood trauma has also been associated with functional deficits in adulthood in patients with schizophrenia (Lysaker et al 2001a;Spence et al 2006;Gil et al 2009;Choi et al 2011).…”
Section: Psychotic Disordersmentioning
confidence: 99%
“…Among patients with borderline personality disorder, rates of adult experiences of abuse are remarkably high and predict failure to achieve symptomatic remission (Zanarini et al 2005). Stain et al (2014) also reported that 45% of first-episode psychosis patients who had experienced childhood trauma also experienced adulthood trauma. This suggests that the damaging effects of trauma on functioning may be initiated in childhood and maintained into adulthood in a large proportion of patients.…”
Section: Revictimizationmentioning
confidence: 99%
“…Emotional abuse was significantly associated with poor premorbid adjustment in late adolescence and overall trauma was significantly correlated with poor general premorbid adjustment. Stain [16] specifically investigated the association between childhood trauma and social functioning in 233 patients with a first-episode of schizophrenia-spectrum disorder and reported that childhood trauma was significantly associated with poorer premorbid social functioning in childhood, early adolescence and late adolescence. Finally, Alameda [17] investigated the relationship between childhood abuse and functional outcome in 225 early psychosis patients.…”
Section: Introductionmentioning
confidence: 99%